PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE BERBASIS STRATEGI RQA TERHADAP KEMAMPUAN KOMUNIKASI TERTULIS DAN HASIL BELAJAR GEOGRAFI - Cantika Oriza Sativa; Bigharta Bekti Susetyo (STKIP Subang, 2026)
This study was motivated by students’ low written communication skills and geography learning outcomes, as well as the dominance of teacher-centered instruction, which has limited student engagement in the learning process. This study aimed to determine the effect of the Think Pair Share cooperative learning model based on the Reading, Questioning, and Answering (RQA) strategy on the written communication skills and geography learning outcomes of tenth-grade students at SMA Negeri 8 Padang on the lithosphere topic. This study employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 39 students in the experimental class and 39 students in the control class. The experimental class was taught using the Think Pair Share cooperative learning model based on the RQA strategy, while the control class received conventional instruction. Data were collected through essay tests and documentation and analyzed using normality, homogeneity, Independent Samples t-test, and N-Gain analyses. The results showed that the data were normally distributed and homogeneous. The Independent Samples t-test yielded significance values of 0.032 for written communication skills and 0.037 for learning outcomes (p < 0.05), indicating that the TPS-RQA model significantly affected both variables. Furthermore, the N-Gain analysis showed that the experimental class achieved a score of 60.60%, compared with 56.28% in the control class. Therefore, the Think Pair Share cooperative learning model based on the RQA strategy significantly improved students’ written communication skills and geography learning outcomes on the lithosphere topic.